Coaching the Best Swimmer of All Time: Michael Phelps - Bowman, B. (2016)
Bob Bowman, Men`s Olympic Head Coach, USA Swimming talks about "Coaching the Best Swimmer of All Time: Michael Phelps" at the FINA Golden Coaches Clinic 2016 (1:30:58 h).